Permafrost degradation amplifies infrastructure-related inequalities across the Qinghai-Tibet Plateau - Xinlong Du; Chunling Zhang; Yunjie Jia; Yuguo Wei; Jinyue Song; Mei Mu; Xiaoqing Peng; Zongxing Li; Peng Zhang; Lin Liu; Zhuoxuan Xia; Rongkun Liu; et al. (Global Environmental Change, 2026)

Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

Underestimated small thermokarst lakes of the Qinghai-Tibet Plateau and their carbon emission potential - Xiaoqing Peng; Hengxing Luo; Weiwei Tian; Zhuoxuan Xia; Oliver W. Frauenfeld; Cuicui Mu; Lin Liu; Jing Luo; Lingcao Huang; Qinshan Zhao; Yimiao Yin (Global and Planetary Change, 2026)

Species-dependent growth rates regulate community biomass under long-term warming and wetting in alpine meadow on the Qinghai-Tibet Plateau - Mingming Shi; Cuicui Mu; Bingrong Zhou; Xiaodong Li; Yunqiao Ma; Mei Mu; Jinyue Song; Xinlong Du; Huakun Zhou (Plant and Soil, 2026)

Quantifying the impacts of increasing light and moderate rainfall on permafrost thermal regimes over the Qinghai-Tibet Plateau: A controlled sensitivity study - Guofei Zhang; Cuicui Mu; Yining Zhang; Xiaofan Zhu; Yi Zhao; Zhuotong Nan (Journal of Hydrology, 2026)

Unravelling methylmercury formation in high-altitude Tibetan thermokarst lakes - Xia Lu; Xiaosha Liu; Zhixia Yang; Liang Li; Man Yang; Yu-Rong Liu; Baohua Gu; Cuicui Mu (Journal of Hazardous Materials, 2026)

Aridity controls on the dominance of soil mineral-associated and particulate organic carbon in the Qinghai-Tibet Plateau - Hebin Liu; Mei Mu; Cuicui Mu; Kun Li; Yuguo Wei; Pengsi Lei; Fumei Liu; Xinlong Du; Shijie Li; Jianyu Li (Global and Planetary Change, 2026)

Time-Series models for ground subsidence and heave over permafrost in InSAR Processing: A comprehensive assessment and new improvement - Chengyan Fan; Cuicui Mu; Lin Liu; Tingjun Zhang; Shichao Jia; Shengdi Wang; Wen Sun; Zhuoyi Zhao (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

The infrastructure cost of permafrost degradation for the Northern Hemisphere - Haodong Jin; Xiaoqing Peng; Oliver W. Frauenfeld; Yuan Huang; Lei Guo; Jing Luo; Guoan Yin; Guohui Zhao; Cuicui Mu (Global Environmental Change, 2024)

Detection, mapping, and interpretation of the main drivers of the Arctic GPP change from 2001 to 2019 - Dujuan Ma; Xiaodan Wu; Gaofei Yin; Zheng Li; Jingping Wang; Rongqi Tang; Qicheng Zeng; Cuicui Mu (Climate Dynamics, 2024)

Thermokarst lake changes along the Qinghai-Tibet Highway during 1991–2020 - Mei Mu; Cuicui Mu; Pengsi Lei; Xiaoxiao Mo; Yuan Qiao; Xu Chen; Hebin Liu (Geomorphology, 2023)

Spatial and temporal variability in snow density across the Northern Hemisphere - Wenyu Zhao; Cuicui Mu; Li Han; Wen Sun; Yanhua Sun; Tingjun Zhang (CATENA, 2023)

Carbon loss and emissions within a permafrost collapse chronosequence - Mei Mu; Cuicui Mu; Hebin Liu; Haiteng Chi; Yongji Zhu; Jianguo Shang; Chengyan Fan; Xiaodong Wu; Guofei Zhang (CATENA, 2023)

The spatiotemporal scale effect on vegetation interannual trend estimates based on satellite products over Qinghai-Tibet Plateau - Dujuan Ma; Xiaodan Wu; Jingping Wang; Cuicui Mu (Journal of Geographical Sciences, 2023)

High carbon emissions from thermokarst lakes and their determinants in the Tibet Plateau - Cuicui Mu; Mei Mu; Xiaodong Wu; Lin Jia; Chenyan Fan; Xiaoqing Peng; Chien‐Lu Ping; Qingbai Wu; Cunde Xiao; Jianbao Liu (Global Change Biology, 2023)
Thermokarst lakes are potentially important sources of methane (CH 4 ) and carbon dioxide (CO 2 ). However, considerable uncertainty exists regarding carbon emissions from thermokarst lakes owing to a limited understanding of their patterns and motivators. In this study, we measured CH 4 and CO 2 diffusive fluxes in 163 thermokarst lakes in the Qinghai–Tibet Plateau (QTP) over 3 years from May to October. The median carbon emissions from the QTP thermokarst lakes were 1440 mg CO 2 m −2 day −1 and 60 mg CH 4 m −2 day −1 , respectively. The diffusive rates of CO 2 and CH 4 are related to the catchment land cover type. Sediment microbial abundance and hydrochemistry explain 51.9% and 38.3% of the total variance in CH 4 diffusive emissions, respectively, while CO 2 emissions show no significant relationship with environmental factors. When upscaling carbon emissions from the QTP thermokarst lakes, the annual average CH 4 release per lake area is equal to that of the pan‐Arctic region. Our findings highlight the importance of incorporating in situ observation data with different emission pathways for different land cover types in predicting carbon emissions from thermokarst lakes in the future.

Performance and changes of high‐resolution (1 km) surface air temperature in Northern Hemisphere permafrost regions - Haodong Jin; Xiaoqing Peng; Oliver W. Frauenfeld; Yaohua Zhao; Xuanjia Li; Weiwei Tian; Cong Chen; Benben Liang; Xiaodong Li; Cuicui Mu (International Journal of Climatology, 2023)
Surface air temperatures are significant indicators of environmental and climatic change that affect a diverse set of physical systems including permafrost. Most temperature products, such as gridded or reanalysis data, are still at a relatively low spatial resolution, limiting the ability to simulate heterogeneous permafrost changes and leading to large uncertainties. Here we apply a downscaling method based on elevation to obtain high‐resolution surface air temperatures from the sixth Coupled Model Intercomparison Project in Northern Hemisphere permafrost regions. Root‐mean‐square errors and mean absolute errors after downscaling are reduced by 34 and 37%, respectively, relative to meteorological site data and gridded observations from the Climatic Research Unit. Compared to the downscaled surface air temperature data, nondownscaled model projections overestimate by 0.12–0.39°C in the discontinuous, isolated, and sporadic permafrost regions and underestimate up to 0.18°C in the continuous permafrost region under different emission scenarios. The warming rates in Northern Hemisphere permafrost regions were 0.093°C/10 year during the historical (1850–2014) period and are projected to be 0.22°C/10 year for SSP1‐2.6, 0.48°C/10 year for SSP2‐4.5, 0.75°C/10 year for SSP3‐7.0, and 0.95°C/10 year for SSP5‐8.5 during 2015–2100, which is 1.4–1.6 times the warming of nonpermafrost regions. Warming rates in high latitudes are 1.2–1.7 times higher than those in high‐elevation regions. Continuous permafrost regions' warming will be 1.2–1.4 times higher than in other permafrost regions. For permafrost with high ground ice content, warming will be 1.1 times greater than in permafrost regions with medium or low ground ice content.

Mobilization of water affecting formation and dissociation of hydrate in clay sediment - Peng Zhang; Xueping Chen; Lianhai Zhang; Shuaijun Li; Wenting Chen; Qingbai Wu; Shuanshi Fan; Rui Bao; Cuicui Mu (Chemical Engineering Journal, 2023)

Accumulation pattern and risk assessment of metal elements in permafrost-affected soils on the Qinghai-Tibet Plateau - Wenjuan Wang; Evgeny Abakumov; Xiaodong Wu; Xiaowen Ji; Cuicui Mu; Xiaofan Zhu; Gensheng Li (CATENA, 2023)

Expression and localization of amelotin, laminin γ2 and odontogenesis-associated phosphoprotein (ODAPH) on the basal lamina and junctional epithelium - Cong Li; Yan Gao; Zhenzhen Xu; Yuan Tian; Haiyu Mu; Cuicui Yu; Yuguang Gao; Li Zhang (Journal of Molecular Histology, 2022)

Acceleration of thaw slump during 1997–2017 in the Qilian Mountains of the northern Qinghai-Tibetan plateau - Cuicui Mu; Jianguo Shang; Tingjun Zhang; Chengyan Fan; Shufa Wang; Xiaoqing Peng; Wen Zhong; Feng Zhang; Mei Mu; Lin Jia (Landslides, 2020)

Changes of soil thermal and hydraulic regimes in the Heihe River Basin - Xiaoqing Peng; Cuicui Mu (Environmental Monitoring and Assessment, 2017)